2020
DOI: 10.1038/s41598-020-70312-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites profiling and pharmacokinetics of troxipide and its pharmacodynamics in rats with gastric ulcer

Abstract: Troxipide is widely used to treat gastric ulcer (GU) in the clinic. However, a lack of systematic metabolic, pharmacokinetic and pharmacological studies limits its clinical use. This study aimed to firstly explore the metabolic, pharmacokinetic and pharmacological mechanisms of troxipide in rats with GU compared to normal control (NC) rats. First, metabolic study was perormed by a highly selective, high-resolution mass spectrometry method. A total of 45 metabolites, including 9 phase I metabolites and 36 phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…identified the 45 phase I and II metabolites of troxipide by using UHPLC‐Q‐TOF‐MS through accurate mass measurements and MS/MS fragmentation interpretation by analyzing plasma, fecal, and urine samples to understand the metabolic pathways of the drug. This is the first time these 45 metabolites have been reported for troxipide thereby filling an information gap 62 …”
Section: Post‐approval Analyses and Hrms Quantificationmentioning
confidence: 90%
See 2 more Smart Citations
“…identified the 45 phase I and II metabolites of troxipide by using UHPLC‐Q‐TOF‐MS through accurate mass measurements and MS/MS fragmentation interpretation by analyzing plasma, fecal, and urine samples to understand the metabolic pathways of the drug. This is the first time these 45 metabolites have been reported for troxipide thereby filling an information gap 62 …”
Section: Post‐approval Analyses and Hrms Quantificationmentioning
confidence: 90%
“…61 Troxipide is a therapeutic agent for gastritis and gastric ulcer. 62 Detailed studies concerning metabolites, pharmacokinetics, and mechanism are missing thereby limiting the clinical use of the drug. Guo et al identified the 45 phase I and II metabolites of troxipide by using UHPLC-Q-TOF-MS through accurate mass measurements and MS/MS fragmentation interpretation by analyzing plasma, fecal, and urine samples to understand the metabolic pathways of the drug.…”
Section: Further Drug Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Heat shock proteins (HSPs) are emerging as crucial regulators of gastric inflammation and ulcer healing. 9 However, unlike other HSPs such as HSP70 25 and HSP90, 26 the specific role of HSP27 in gastric ulcer remains unclear. Herein, we found that HSP27 contributes to ulcer healing by promoting cell proliferation, migration and angiogenesis, suggesting its potential involvement in stressinduced gastric ulcer through modulation of the CXCL12/CXCR4 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) infection is considered to be the most important risk factor for the development of PUD and the prevalence of the infection is as high as 90% in developing countries. [4][5][6] Patients with PUD may remain asymptomatic or symptomatic, and because of undefined risk factors along with a lack of specific symptoms at the early stages, the diagnosis is often delayed, leading to poor prognosis and high rates of recurrence of the disease. [7][8][9] However, the conventional endoscopic with biopsy-based invasive methods are not only suitable for early diagnosis, but also inappropriate for widespread population-screening including infants, children, pregnant women, and seniors.…”
Section: Introductionmentioning
confidence: 99%